The propagandistic narration of the defeat of the Spanish Armada and the mythical construction of sir Francis Drake in Romantic Britain - Ruiz Mas, José (Cuadernos de Ilustración y Romanticismo, 2023)
In this article, I analyse the literary images of the Spanish Armada and of one of its main English protagonists, Sir Francis Drake, as perceived and depicted by Robert Southey and by a number of British Romantic poets, travel and short story writers (George Lipscomb, Lord Byron, Thomas Babington Macaulay, Joseph Train, Mrs Anna Eliza Bray and Christian Isobel Johnstone). In their literary descriptions of the alleged Spanish naval disaster in 1588, they spread the English “victory” to a wider and a younger readership and mocked Spain’s past naval hegemony. As far as the depiction of the legendary Drake, they insisted on presenting an idealised version of the English hero. I explain the gradual Romantic construction of two popular English myths that are still rampant in the British imaginary: the uncontested English victory on the Spanish Armada in 1588 and the deification of the persona of Drake, a process in which Southey took a leading role.